2000
DOI: 10.1037/0022-0663.92.3.478
|View full text |Cite
|
Sign up to set email alerts
|

The role of task-avoidant and task-focused behaviors in the development of reading and mathematical skills during the first school year: A cross-lagged longitudinal study.

Abstract: The aim of the study was to examine whether children's achievement strategies would prospectively predict their improvement in reading and mathematical skills during the 1st school year, or whether it is rather the skills that predict the change in their achievement strategies. One hundred five 6-to 7-year-old children were investigated 3 times during the 1st school year. Each time, their reading and mathematical skills were tested, and their task-avoidant versus task-focused behaviors were rated by their clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
175
6
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(200 citation statements)
references
References 86 publications
(199 reference statements)
17
175
6
2
Order By: Relevance
“…However, it is also possible that task avoidance taps self-regulation or inattention that co-exists with reading and spelling disability (e.g., Willcutt et al, 2007). Previous studies have shown links between task avoidance and reading (e.g., Onatsu-Arvilommi & Nurmi, 2000) as well as between task avoidance and spelling (e.g., Georgiou et al, 2010;Liao et al, 2013). In this study, however, the RD group did not demonstrate task avoidance.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…However, it is also possible that task avoidance taps self-regulation or inattention that co-exists with reading and spelling disability (e.g., Willcutt et al, 2007). Previous studies have shown links between task avoidance and reading (e.g., Onatsu-Arvilommi & Nurmi, 2000) as well as between task avoidance and spelling (e.g., Georgiou et al, 2010;Liao et al, 2013). In this study, however, the RD group did not demonstrate task avoidance.…”
Section: Discussioncontrasting
confidence: 52%
“…Several studies investigating student's motivation have also shown that task avoidance, the extent to which a child chooses to avoid approaching or completing a task rather than investing effort, particularly as task demands increase, is a unique predictor of reading (e.g., Georgiou, Manolitsis, Zhang, Parrila, & Nurmi, 2013;Onatsu-Arvilommi & Nurmi, 2000) and spelling (e.g., Georgiou, Manolitsis, Nurmi, & Parrila, 2010;Liao, Georgiou, Zhang, & Nurmi, 2013). Reading proficiency in Finnish can be achieved relatively effortlessly (Lerkkanen et al, 2004), but learning to spell poses more difficulties for children (Aro, 2004;in press).…”
Section: The Present Studymentioning
confidence: 99%
“…Boys have also been reported to score higher on task-avoidant behaviors (e.g., Onatsu-Arvilommi & Nurmi, 2000), whereas helpless behaviors or passive avoidance may be more common to girls (Dweck, 1986). In the present study, boys were rated higher on distractibility, negative emotionality, and task avoidance.…”
Section: Temperament Affects and Behaviors 18supporting
confidence: 52%
“…The motivation literature describes a few types of such achievement-related motivation. One such motivational construct is task persistence (as opposed to task avoidance), which can be characterized as a type of behavior that a child exhibits when completing learning tasks, such as by showing effort and staying determined when facing challenges (Onatsu-Arvilommi & Nurmi, 2000;Zhang, Nurmi, Kiuru, Lerkkanen, & Aunola, 2011). Task persistence in school tasks is a form of effortful control (e.g., Drake, Belsky, & Fearon, 2014) and has mainly been studied as a general construct, not subject-specific.…”
Section: Role Of Perceived Parental Involvement In Children's Math Pementioning
confidence: 99%